The biological complexity of RKIP signaling in human cancers - Farooqi, Ammad Ahmad (Exp Mol Med, 2015)
The Raf kinase inhibitory protein (RKIP) has been demonstrated to modulate different intracellular signaling pathways in cancers. Studies have shown that RKIP is frequently downregulated in cancers; therefore, attempts have been made to upregulate the expression of RKIP using natural and synthetic agents for the treatment of human malignancies. Moreover, various regulators such as specific proteins and microRNAs (miRNAs) that are involved in the regulation of RKIP expression have also been identified. RKIP mechanistically modulates the apoptotic regulators of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) signaling. Because of its critical role in human cancers, RKIP has drawn much research attention, and our understanding is expanding rapidly. Here, we summarize some of the biological complexities of RKIP regulation. However, we restrict our discussion to selected tumors by focusing on TRAIL, miRNAs and natural agents. Emerging evidence suggests a role for natural agents in RKIP regulation in cancer cells; therefore, naturally occurring agents may serve as cancer-targeting agents for cancer treatment. Although the literature suggests some advancement in our knowledge of RKIP biology, it is incomplete with regard to its preclinical and clinical efficacy; thus, further research is warranted. Furthermore, the mechanism by which chemotherapeutic drugs and novel compounds modulate RKIP and how nanotechnologically delivered RKIP can be therapeutically exploited remain to be determined.